Strategi daya tindak dalam kalangan ibu tunggal kematian pasangan / Dharatun Nissa Puad Mohd Kari - Dharatun Nissa, Puad Mohd Kari (2017)
The purpose of this study is to explore the meaning of being single mothers due to the death of a spouse. The study also aims to explore the coping strategies used by single mothers in handling issues and challenges. The phenomenological approach was used to gather the data. Participants included six single mothers who met the following three criteria: 1) they have experienced the death of a spouse, 2) they must have at least one child from the marriage and 3) they have been single mothers for a minimum period of one year. Data was gathered from semi structured interviews and document analysis. The data was then analyzed using Atlas.ti 7. Seven themes emerged from the analysis. Three of the themes answered research question number 1 which is: ‘What does it mean to be a single mother?’. The themes are; the perception of being a single mother, the role of a single mother and the challenges of being a single mother. Another four themes answered research question number 2, which is: ‘What are the coping strategies used by single mothers to handle issues and challenges?’. The themes are; adopting a spiritual approach, making emotional and cognitive adjustments, having a social support system which consists of various parties and possessing positive behaviour. In summary, single mothers who have experienced the death of a spouse are able to cope with the challenges that they face depending on their perceptions of their ability to cope. The implication of this study can be divided into two aspects; 1) the implications in terms of knowledge and practice of counselling and 2) implications for future researchers. The knowledge gained from this study would help practicing counselors to have a better understanding of single mothers who have experienced the death of a spouse. Practicing counselors may help single mothers to choose suitable coping strategies. Practicing counsellors may also develop appropriate intervention and psycho educational modules that can be applied in counselling sessions. Since this study focused on Malay single mothers whose spouse have died, future researchers may consider exploring coping strategies used by single mothers from different cultural backgrounds.